The Influence of a Project-Based Learning Model in Science and Social Studies on Adoption of Students’ Procedural Knowledge - Banđur, Veljko R.; Ristanović, Dušan P.; Stanojević, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Training students to independently explore and analyze natural and social phenomena and processes is one of the more important and demanding tasks of science and social studies teaching. In order to successfully accomplish this formulated task, it is necessary for students to acquire the appropriate level of procedural knowledge, i.e. to know how to plan and conduct a research. Starting from the fact that the project work in the current reform of education in Serbia has become a mandatory teaching activity, the paper presents the results of an experimental research aimed at determining the efficiency of the project-based learning model in science and social studies in the process of acquiring procedural knowledge of students. The research was carried out on a sample of 72 students of the experimental group (three classes where the contents of the science and social studies was delivered according to the project-based learning model) and 70 students of the control group (three classes where the same contents was delivered through the usual group tasks) of the fourth grade of primary school. It turned out that, after the implementation of the experimental program, the achievements of the students of the experimental group improved in all three categories of procedural knowledge – the knowledge of different ways of collecting data, the knowledge of how to sort the research data, and the knowledge of how to present the research results.
Keywords: project-based learning model; science and social studies; procedural knowledge; research work of students